Children in the mountains: high mountain trekking holidays are best avoided for the very young. - Pollard, Andrew J.; Murdoch, David R.; Bärtsch, Peter (The BMJ, 1998)
Editorial p 873 - - High altitude areas of the world were once visited only by a privileged minority. Now the great mountain ranges have become popular tourist destinations. An increasing number of children accompany their parents on such journeys, but little consideration has been paid to the potential risks of exposing young children to high altitudes. We are aware of ascents in Nepal where infants have been carried to over 6000 m on mountains requiring technical snow mountaineering expertise. - - About half the adult tourists on the popular trekking routes in Nepal develop acute mountain sickness,1-3 a disorder characterised by headache, nausea, vomiting, anorexia, fatigue, dizziness, and sleep disturbance that is particularly common above 2500 m, especially when ascent is rapid.4 Although acute mountain sickness is generally benign, it may progress to life threatening high altitude cerebral or pulmonary oedema. Little information exists about altitude illness in children. Wu studied 464 children travelling across the Tibetan plateau at 4550 m and found incidences of acute mountain sickness and high …